Formulation and evaluation of salicylic acid suspension using Araucaria heterophylla gum as a suspending agent: Research Article (Journal of Pharma Insights and Research, 2023)
Suspensions serve as a means to improve the bioavailability of poorly soluble drugs, utilizing a variety of suspending agents derived from natural, synthetic, and semisynthetic sources. In this investigation, the potential of Araucaria heterophylla mucilage, a natural origin suspending agent, was explored to enhance the in-vitro permeability of salicylic acid, serving as a model poorly soluble drug. The suspensions were formulated using the trituration method with concentrations of 0.5%, 1%, and 2% of the suspending agent. Comparative analyses were conducted with acacia, a natural suspending agent, and HPMC 50 cps, a synthetic suspending agent, at equivalent concentrations. Physical and chemical assessments, encompassing particle size analysis, viscosity, physical stability studies, assay, and in-vitro drug permeability studies, were applied to all suspensions. The outcomes revealed that Araucaria heterophylla mucilage, when utilized as a suspending agent at a concentration of 2% (F6), exhibited a reduced particle size, favorable viscosity, heightened in-vitro drug permeability, and commendable physical stability compared to the other formulated suspensions. Consequently, F6 was deemed the final formulation, with Araucaria heterophylla mucilage recognized as the preferred suspending agent relative to acacia and HPMC, given its superior characteristics. Notably, F6 demonstrated a nearly 2.4-fold increase in in-vitro permeability compared to the suspension devoid of a suspending agent (F10)